A new system to measure the gradient vector of the magnetic field on unmanned aerial vehicles – data processing and field experiment. Issue 1 (22nd November 2022) - Kulüke, Christian; Virgil, Christopher; Stoll, Johannes; Hördt, Andreas
Abstract: We present a novel airborne magnetometer system deployed on an unmanned aerial vehicle (UAV) that is capable of measuring the horizontal gradient of the three components of the magnetic field. The system consists of two three-component fluxgate magnetometers (FGM) that are mounted on a transverse horizontal boom. The sensor attitude is determined with a low-cost inertial measurement unit. The estimation of the magnetic field components as well as its gradient is extremely sensitive to sensor movement and sensor rotation and requires sophisticated data processing and corrections. Here, we present four specific calibration and correction procedures we consider essential to achieve sufficient accuracy. First, we present a new in-flight calibration method for an FGM gradiometer. Second, we introduce a procedure that corrects for rotation-induced noise in the FGMs that has not been described previously in the literature. In a third step, we correct for mechanical vibrations, which induce high-frequency noise in the data. Finally, the gradient of each component is mathematically rotated into the geographical coordinate system. The performance of the system is evaluated on a test site where several metal objects of known magnetization were placed on the ground surface. For the first time, we show the gradients of magnetic field components measured on a UAV. The gradients agree with the results of a forward simulation within a few nT m −1 . The accuracy will be sufficient for many practical applications, such as geological mapping, ore exploration, and the search for metallic bodies.